Hybrid Orchestration in Multi-stakeholder Innovation Networks: Practices of mobilizing multiple, diverse stakeholders across organizational boundaries - Reypens, Charlotte; Lievens, Annouk; Blazevic, Vera (Organization studies, 2021)
The prominence of inter-organizational networks for innovation raises questions about how to support collaboration between multiple, diverse stakeholders. We focus on network orchestration and examine the practices that support orchestrators in dealing with the challenges brought by the number and diversity of stakeholders. Using qualitative, longitudinal data from an innovation network of 57 stakeholders, we identify three types of orchestration practices – connecting, facilitating and governing – and observe how they underlie innovation trajectories over time, each supporting the achievement of distinct network outcomes. Within and across trajectories, we observe how orchestrators rely on hybrid orchestration: they switch between dominating and consensus-based orchestration modes, in response to emergent network challenges. By switching between modes, orchestrators address the complexities of simultaneously and temporally dealing with a large number and diversity of stakeholders. With these findings, we present a toolbox of practices for network orchestrators to address distinct challenges in different types of networks and underscore that network research should consider the plurality of networks, rather than treat them as universalistic. Orchestrators play a key role in managing this plurality: they act as environmental scanners who address emergent network challenges through hybrid orchestration. This realization opens new avenues for network research, for example, relating to the skills and capabilities of orchestrators.